Never work harder than your students : the journey to great teaching - Smith, Janie Ray.; Jackson, Robyn Renee; Association for Supervision and Curriculum Development (Alexandria, Va. : ASCD, 2009)
Explores real-world examples of teachers in the classroom using Robyn Jackson's principles for great teaching. Classroom and coaching scenes at the elementary, middle, and high school levels illustrate the principles in action.
Introduction (2:14) -- Start where your students are (11:22) -- Know where your students are going (5:05) -- Expect to get your students there (5:56) -- Support your students (7:24) -- Use effective feedback (9:05) -- Focus on quality, not quantity (8:00) -- Never work harder than your students (10:34) -- Putting it all together (5:19).
Host, Robyn Jackson.
Content expert, Janie Ray Smith.
Videodisc version record.
In English.
Keywords: Effective teaching; Teacher effectiveness; Enseignement efficace; Enseignants -- Efficacité.; Effective teaching; Teacher effectiveness; Educational films; Educational films; Films éducatifs.